Digital Marketing - Chaffey, Dave; Ellis-Chadwick, Fiona (Pearson International Content, 2022)
Discover more about effective Digital Marketing strategies and practices, and expand your knowledge of the field, learning from the success stories of some of the biggest brands. Digital Marketing, 8th edition is a market-leading text, providing you with the most comprehensive guide to the strategies, techniques, and online trends that have transformed the way companies communicate with their consumer audiences today. The text, known for its clear structure and accessible content, offers you valuable insight into the main principles and aspects of Digital Marketing. The eighth edition has been comprehensively updated to help you learn more about the success factors of a digital marketing strategy, using key techniques in the area, including search, social media and content marketing, conversion optimisation, and marketing automation. It also introduces increased data-driven marketing techniques with many new examples covering digital analytics, artificial intelligence, and machine learning. This latest edition also links marketing theory with practical business experience to help you understand digital marketing in the real world through case studies from market-leading and cutting-edge companies such as ASOS, Spotify, and L'Oreal. Many useful features include self-assessment exercises and discussion questions to self-test your knowledge and understanding of the topics. With the 'Essential Digital Skills' boxes guiding you into developing key skills you will later need in the workplace, this leading textbook is a must-have guide for students and professionals. Pearson, the world's learning company.